Synthetic Approaches to Organoselenium Derivatives with Antimicrobial and Anti-Biofilm Activity - Di Leo, Iris; Messina, Federica; Nascimento, Vanessa; Nacca, Francesca G.; Pietrella, Donatella; Lenardão, Eder J.; Perin, Gelson; Sancineto, Luca (Mini-Reviews in Organic Chemistry, 2019)
In the recent years, an increasing attention has been given to the biological activities exerted by organoselenium compounds. In 1984, Sies reported for the first time the ability of ebselen to mimic the activity of glutathione peroxidase. From this milestone, several studies reported the pharmacological properties of selenium-containing compounds including their exploitation as antimicrobials. In this context, this minireview presents the most recent examples of seleno derivatives endowed with antimicrobial activities while discussing the most interesting and recent synthetic procedures used to obtain these compounds.
Keywords: gram-positive bacteria